TEOLOGI KEMAKMURAN DALAM KITAB SARASAMUCCAYA - I Wayan Bagus Citra Wedana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This article discusses the theology of prosperity from the perspective of the Sarasamuccaya as an essential Hindu text. The study emphasizes that prosperity is not merely material achievement but a balance between dharma, artha, kama, and moksa. Using a hermeneutical approach, this research reveals that the Sarasamuccaya provides an ethical and spiritual framework in managing wealth while highlighting dharma as the foundation for achieving well-being. The findings indicate that true prosperity must be grounded in dharma, leading humans to both worldly happiness and spiritual liberation (moksa).